Enhancing MSME Sales Performance on E-commerce Platforms: Exploring the Interplay of Digital Skills, Product Innovation, and User Experience - Titin, Titin; Ausat, Abu Muna Almaududi; Wanof, M. Indre; Syamsuri, Syamsuri; Kraugusteeliana, Kraugusteeliana (Applied Information System and Management (AISM), 2025)
This study aims to analyze the relationship between digital skills, product innovation, and user experience with the sales performance of MSMEs (Micro, Small, and Medium Enterprises) on e-commerce platforms in Semarang. Based on the Resource-Based View (RBV) and Diffusion of Innovations (DOI) theories, this study uses quantitative methods with Structural Equation Modeling-Partial Least Squares (SEM-PLS) techniques to analyze data from 100 MSMEs active on digital platforms. The results showed that digital skills have a positive and significant impact on sales performance, as they are able to assist MSMEs in optimizing digital marketing and online transaction processes efficiently. In addition, product innovation also makes an important contribution by aligning products with consumer needs and preferences, thereby driving customer loyalty and expanding market share. User experience (UX) also plays a crucial role in influencing customer satisfaction levels and the likelihood of repeat purchases, which directly impacts sales. The findings confirm that MSMEs need to prioritize digital skills development, continuous product innovation, and e-commerce platform optimization to remain competitive in the growing digital economy. This research contributes to the literature by offering an integrated framework of how digital capabilities can help MSMEs to stay competitive in the digital economy.